2004
DOI: 10.1037/0022-006x.72.5.897
|View full text |Cite
|
Sign up to set email alerts
|

Physically Abusive Mothers' Responses Following Episodes of Child Noncompliance and Compliance.

Abstract: The authors used sequential analysis to examine specific interaction patterns between physically abusive mothers and their children following episodes of noncompliance and compliance. Fifteen abusive and 15 nonabusive, low-risk mother-child dyads were observed, and their behaviors were coded for specific interactions. The children in the study ranged in age from 2 to 6 years. Results indicated that after noncompliance occurred, physically abusive mothers were more likely than nonabusive mothers to respond nega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 13 publications
1
28
0
Order By: Relevance
“…Child behaviors included compliance (complying with command within 5 seconds), noncompliance (not complying with commands within 5 seconds) and deviance (e.g., negative talk, touch, whining, yelling). Maternal responses to child behavior were defined as any maternal discrete behavior occurring within 5 seconds following the initiation of child compliance or noncompliance (Borrego, Timmer, Urquiza, & Follette, 2004). Maternal non-response (i.e., ignore) was coded if the mother did not respond within 5 seconds to the initiation of child compliance or noncompliance.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Child behaviors included compliance (complying with command within 5 seconds), noncompliance (not complying with commands within 5 seconds) and deviance (e.g., negative talk, touch, whining, yelling). Maternal responses to child behavior were defined as any maternal discrete behavior occurring within 5 seconds following the initiation of child compliance or noncompliance (Borrego, Timmer, Urquiza, & Follette, 2004). Maternal non-response (i.e., ignore) was coded if the mother did not respond within 5 seconds to the initiation of child compliance or noncompliance.…”
Section: Methodsmentioning
confidence: 99%
“…After contingent sequences of behavior are discovered, researchers attempt to estimate the association between interaction patterns and explanatory factors (such as group membership)—in this study, maternal depression status. Sequential analysis presents several strengths as a method of understanding parent-child interactions (Borrego et al, 2004). It takes into account discrete behaviors rather than global ratings of parenting behaviors and provides contextual information regarding parenting behavior beyond the more static representations of frequency counts and dimensional ratings (Borrego et al, 2004; Urquiza & Timmer, 2002).…”
Section: Methodsmentioning
confidence: 99%
“…The researchers observed parents and children engaged in short, structured play sessions in order to compare everyday interactions (Borrego, Timmer, Urquiza, & Follett, 2004;Wilson et al, 2009). We observed and videotaped mother-child and father-child interactions in the family homes.…”
Section: Procedures and Research Sitesmentioning
confidence: 99%
“…Over time, abusive parents respond to this pattern with increasingly intense physical discipline in an ill-fated attempt to regain control (Reid, 1986). Abusive parents also fail to consistently reinforce positive child behaviors, being as likely to criticize (''it's about time'') as to respond positively (''good job'') in the conversational turn after their child complies with a request (Borrego, Timmer, Urquiza & Follette, 2004;Oldershaw, Walters, & Hall, 1986).…”
Section: Unanswered Questions Regarding Maltreated Children's Behaviormentioning
confidence: 89%
“…Most studies with mixed structure reported findings averaged across multiple tasks (e.g., Borrego et al, 2004;Coster, Gersten, Beeghly, & Cicchetti, 1989;Lau et al, 2006;Schindler & Arkowitz, 1986); hence, for those studies that did report separate comparisons for each task (e.g., Mash, Johnston, & Kovitz., 1983) effect sizes were computed for each task and then averaged to obtain an overall effect size for that study.…”
Section: Notesmentioning
confidence: 97%